(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
This article researches the understanding and evaluation of tf mathematics history and its applying to the higher mathematics teaching, discusses the significance and role of history of mathematics in higher mathematics teaching, researches the method and means which the history of mathematics is introduced into higher mathematics teaching.